HUBUNGAN ANTARA KEPUASAN KERJA DAN KOMITMEN ORGANISASI DENGAN INTENSI TURNOVER PADA GURU - YULIA SAFITRI, REZKY (Character Jurnal Penelitian Psikologi, 2013)
Abstract This study aimed to test wheter the relationship between work satisfaction and organizational commitment with the Turnover intention of the teachers. There are two independent variables and one dependent variable: (1) Work Satisfaction, (2) Organizational Commitment, and (3) Turnover Intention. This research uses the scales of Work Satisfaction, Organizational Commitment, and Turnover Intention which is designed to measure the Work Satisfaction, Organizational Commitment, and Turnover Intention. This research uses the quantitative method. The samples used in this research are 48 part-time teachers in the organization of PGRI 10 Junior High School Candi, Sidoarjo. The data are analyzed using Double Regression technique with the IBM SPSS Statistics 20 program. The research result shows that there is a significant relation between Work Satisfaction and Organizational Commitment with Turnover Intention. Work Satisfaction has a negative significant relationship with Turnover Intention and Organizational Commitment does not have any significant relationships with the Turnover Intention since the significance result is (p) 0,545 which means P value > 0,05 so it is considered that it does not have any significant relationships with the Turnover Intention. Keywords: Work Satisfaction, Organizational Commitment, Turnover Intention. Abstrak Penelitian ini bertujuan untuk menguji hubungan antara Kepuasan Kerja dan Komitmen Organisasi dengan Intensi Turnover pada Guru. Terdapat dua variabel bebas dan satu variabel terikat yaitu : (1) Kepuasan Kerja, (2) Komitmen Organisasi, dan (3) Intensi Turnover. Penelitian ini menggunakan skala Kepuasan Kerja, Komitmen Organisasi, dan Intensi Turnover yang disusun guna mengukur Kepuasan Kerja, Komitmen Organisasi, dan Intensi Turnover. Penelitian ini menggunakan metode kuantitatif. Sampel yang digunakan dalam penilitian ini ialah 48 guru tidak tetap di SMP PGRI 10 Candi, Sidoarjo data dianalisis menggunakan teknik Regresi Berganda dengan program IBM SPSS Statistics 20. Hasil dari penilitian ini menunjukkan adanya hubungan yang signifikan antara Kepuasan Kerja dan Komitmen Organisasi dengan Intensi Turnover, Kepuasan kerja memiliki hubungan yang signifikan dan negatif dengan Intensi Turnover selanjutnya Komitmen organisasi tidak berhubungan signifikan dengan Intensi Turnover karena hasil signifikansi (p) 0,545 berarti P value > 0,05 sehingga dinyatakan tidak berhubungan signifikan dengan Intensi Turnover. Kata kunci: Kepuasan Kerja, Komitmen Organisasi, Intensi Turnover